2014
DOI: 10.1038/bjc.2014.539
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of nucleostemin contributes to an advanced malignant phenotype and a poor prognosis in oral squamous cell carcinoma

Abstract: Background:Nucleostemin (NS) is essential for the maintenance of stem cell properties, the functions of which remain poorly understood in cancer cells. The purpose of this study was to explore the impact of NS on malignancy and its clinical significance in oral squamous cell carcinoma (OSCC) patients.Methods:We investigated the effects of NS on the proliferation and invasion of OSCC using NS-overexpressing or -knockdown OSCC cells. We assessed the activation of the STAT3 (signal transducer and activator of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…All of the patients were preoperatively treated with a total dose of 30 Gy of concurrent chemoradiotherapy followed by curative surgery as a phase II study (Nagata et al , 2011; Yoshida et al , 2014). Radiotherapy was administered at a daily dose of 2 Gy five times a week for 15 days.…”
Section: Methodsmentioning
confidence: 99%
“…All of the patients were preoperatively treated with a total dose of 30 Gy of concurrent chemoradiotherapy followed by curative surgery as a phase II study (Nagata et al , 2011; Yoshida et al , 2014). Radiotherapy was administered at a daily dose of 2 Gy five times a week for 15 days.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, blood plasma samples were obtained from 30 of the 52 patients; plasma was separated by centrifugation and stored at −80 • C until subsequent analysis. All patients were treated preoperatively with a total dose of 30 Gy of concurrent chemoradiotherapy, which was followed by curative surgery as a phase II study [38,39]. Radiotherapy was administered daily at 2 Gy five times per week for 15 days.…”
Section: Clinical Samplesmentioning
confidence: 99%
“…Kobayashi et al studied the prognostic effect of NS in invasive breast cancers and reported that cases with positive NS expression exhibited markedly shorter disease-free survival (16). The overexpression of NS in oral squamous cell carcinoma was correlated with advanced T and N stage, and worse prognosis (19). In these reports higher NS expression was associated with malignancy, aggressive behavior, and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%